1985
DOI: 10.1159/000124151
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Modulation of Sexual Behavior by α-Adrenoceptors in Male Rats

Abstract: Clonidine, a commonly used antihypertensive agent believed to act by stimulation of central α- adrenoceptors, produced a dose-related suppression of ejaculatory behavior in sexually vigorous male rats throughout the range of treatment (0.0125–0.5 mg/kg). Treatment with 0.25 mg/kg virtually eliminated ejaculatory behavior, without altering the number of animals mounting and intromitting. These effects were maintained for at least 4 h after treatment. Prazosin, another antihypertensive (but acting by blockade of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
0
4

Year Published

1987
1987
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(88 citation statements)
references
References 20 publications
5
79
0
4
Order By: Relevance
“…For example, yohimbme (which mcreases NE transmission by blocking inhibitory alpha-2 adrenoceptors) was reported to increase the number of mounts after genital anesthet~zatmn, to increase the percentage of sexually naive males mounting, intromltting and ejaculating, and to decrease the latency to mtromisslon [62]. In another study, yohlmbme faclhtated several copulatory rate and ejaculation threshold measures, including decreased ejaculation latency, postejaculatory interval, mtercopulatory interval, and mtromlssions preceding ejaculation, whde the alpha-2 agonist, clonidine (which decreases noradrenergic transmission), was found to decrease the number of males ejaculating [63] In addition, the alpha-I receptor antagonist, prazosm, slowed copulation by increasing intromission and ejaculation latencies and increasing postejaculatory interval [63]. Finally, a recent report demonstrated that three drugs (yohimblne, imiloxan, and idazoxan) which were found to increase sexual arousal, all bound with high affinity to alpha-2 receptors [130].…”
Section: Noradrenergic Influences On Male Sexual Behaviormentioning
confidence: 92%
See 2 more Smart Citations
“…For example, yohimbme (which mcreases NE transmission by blocking inhibitory alpha-2 adrenoceptors) was reported to increase the number of mounts after genital anesthet~zatmn, to increase the percentage of sexually naive males mounting, intromltting and ejaculating, and to decrease the latency to mtromisslon [62]. In another study, yohlmbme faclhtated several copulatory rate and ejaculation threshold measures, including decreased ejaculation latency, postejaculatory interval, mtercopulatory interval, and mtromlssions preceding ejaculation, whde the alpha-2 agonist, clonidine (which decreases noradrenergic transmission), was found to decrease the number of males ejaculating [63] In addition, the alpha-I receptor antagonist, prazosm, slowed copulation by increasing intromission and ejaculation latencies and increasing postejaculatory interval [63]. Finally, a recent report demonstrated that three drugs (yohimblne, imiloxan, and idazoxan) which were found to increase sexual arousal, all bound with high affinity to alpha-2 receptors [130].…”
Section: Noradrenergic Influences On Male Sexual Behaviormentioning
confidence: 92%
“…I-DOPA is the precursor molecule for both DA and NE. That the effects of I-DOPA on male copulatory behavior were not due to an increase in noradrenergic neurotransmission was suggested by the observation that the noradrenergic (alpha-2) agonist, clonidine, had little effect on copulatory behavior at doses that did not affect motor capability ( [139], but see [63] discussed below).…”
Section: Ejje~ Ts Of Catecholamme Pi Ecur~or I-dopamentioning
confidence: 99%
See 1 more Smart Citation
“…A major factor promoting MPOA DA release is (Malmnas, 1976;Mas et al, 1995;Niikura et al, 2002;Rodriguez-Manzo, 1999;Scaletta and Hull, 1990) DA agonists also facilitated copulation in short-term (Malmnas, 1976) and long-term (Scaletta and Hull, 1990) castrated rats. DA antagonists − (Ågmo and Picker, 1990;Ahlenius and Larsson, 1990;Lopez and Ettenberg, 2000, 2002b Noradrenergic NE agonists + (Clark et al, 1984;Clark et al, 1985;Clark, 1995;Rodriguez-Manzo, 1999;Smith et al, 1987;Tallentire et al, 1996) Although noradrenergic drugs appear to facilitate male sexual behavior, high levels of peripheral NE activity inhibit erections (Stefanick et al, 1983) by vasoconstricting penile arteries.…”
Section: Effects Of Systemically Administered Drugs On Male Rat Sexuamentioning
confidence: 99%
“…However, it has been described that the long-term use of clonidine was able to affect the sexual behavior and promotes fertility impairment (Clark et al, 1985;Weiss, 1991). In fact, previous study from our laboratory showed that in vitro treatment with clonidine desensitizes the contractions of rat testicular capsule induced by noradrenaline which could impair the putative transport of spermatozoa from seminiferous tubule to caput of epididymis (Dantas da Silva Junior et al, 2014).…”
Section: Introductionmentioning
confidence: 99%